The Use of Unique, Environmental Lactic Acid Bacteria Strains in the Traditional Production of Organic Cheeses from Unpasteurized Cow’s Milk - Anna Łepecka; Anna Okoń; Piotr Szymański; Dorota Zielińska; Katarzyna Kajak-Siemaszko; Danuta Jaworska; Katarzyna Neffe-Skocińska; Barbara Sionek; Monika Trząskowska; Danuta Kołożyn-Krajewska; Zbigniew J. Dolatowski (Molecules, 2022)
The aim of this study was to use local LAB cultures for the production of organic acid-rennet cheeses from unpasteurized cow’s milk. Under industrial conditions, three types of cheese were produced, i.e., traditionally with acid whey (AW), with starter culture L. brevis B1, or with starter culture L. plantarum Os2. Strains were previously isolated from traditional Polish cheeses. Chemical composition, physico-chemical, microbiological, and sensory studies during 2 months of storage were carried out. As a result of this research, it was found that the basic composition was typical for semi-hard, partially skimmed cheeses. Mainly saturated fatty acids were detected. The cheeses were rich in omega-3, -6, and -9 fatty acids and conjugated linoleic acid (CLA), and were characterized by good lipid quality indices (LQI). All of the cheeses were characterized by a high number of lactic acid bacteria, with Enterobacteriaceae, yeast, molds, and staphylococci contaminants, which is typical microbiota for unpasteurized milk products. Water activity, pH, and total acidity were typical. A lower oxidation-reduction potential (ORP) of cheeses with the addition of strains and stability of the products during storage were observed. The B1 and Os2 cheeses were lighter, less yellow, had a more intense milk and creamy aroma, were softer, moister, and more elastic than AW cheese. The research results indicate the possibility of using environmental LAB strains in the production of high-quality acid-rennet cheeses, but special attention should be paid to the production process due to the microbiological quality of the cheeses.